2019
DOI: 10.1016/j.heliyon.2019.e02462
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on nutrient contents in the different parts of indigenous and hybrid varieties of pumpkin (Cucurbita maxima Linn.)

Abstract: Two varieties (indigenous and hybrid) of pumpkin (Cucurbita maxima) are cultivated and widely used as food sources in Bangladesh. The aim of this study is to compare nutrient contents in different parts of two varieties of pumpkin. The nutritional compositions were analyzed by standard methods. Fatty acids and amino acids were analyzed by GC/MS and amino acid analyzer. The proximate compositions analysis data indicate that a higher amount of moisture (p < 0.001) and fat (p < 0.01) were observed in the seed of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
40
4
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 35 publications
(33 reference statements)
9
40
4
3
Order By: Relevance
“…The result of the mineral analysis shows potassium -2924mg/100g, magnesium -42.41mg, iron -33.35mg/100g and calcium -28.48mg/100g as the predominant minerals with Potassium being the most abundant, similar works by Adubufuor et al [38], Amin et al [39] and Mayer [40] reported Potassium as the most abundant mineral in pumpkin pulp flour. The result for calcium is similar to the value reported by Mayer [40].…”
Section: Physico-chemical Propertiessupporting
confidence: 61%
See 1 more Smart Citation
“…The result of the mineral analysis shows potassium -2924mg/100g, magnesium -42.41mg, iron -33.35mg/100g and calcium -28.48mg/100g as the predominant minerals with Potassium being the most abundant, similar works by Adubufuor et al [38], Amin et al [39] and Mayer [40] reported Potassium as the most abundant mineral in pumpkin pulp flour. The result for calcium is similar to the value reported by Mayer [40].…”
Section: Physico-chemical Propertiessupporting
confidence: 61%
“…The result shows phosphorous as the least abundant at 0.23mg/100g, Amin et al [39] reported similar low value of phosphorous 1.36mg/100g, however Adubufuor et al [38] reported a value of 295.75mg/100g for phosphorous. Manganese 1.06mg/100g and zinc 1.83mg/100g were found to be higher than the 0.40mg/100g for manganese and 0.23mg/100g for zinc reported by Amin et al [39], while the result for sodium at 11.99mg/100g was lower than 20.75mg/g reported by the same work. The variation in the mineral content may be due to changes in agricultural practice, soil types and varieties grown [40].…”
Section: Physico-chemical Propertiesmentioning
confidence: 89%
“… 19 The total ash content of hydrocolloids was between 5.41 and 9.02%, where the samples extracted at pH 3 and 10 presented the highest values and that at pH 7 presented the lowest; this parameter is indicative of physiological minerals, 20 which indicates that the HBSP obtained in alkaline and acid mediums could present the highest amount of sodium, potassium, iron, calcium, or magnesium, the principal minerals identified in the peel of squash. 21 The amount of protein was similar in all case studies, presenting values of 16.32 for pH 3, 18.09 for pH 7, and 18.89 for pH 10. These results obtained are higher than those for guar gum (8.20%), 18 fenugreek seed (7.24%), 22 and xanthan gum (5.40%) and the lowest– for Arabic (2.31%) gum.…”
Section: Resultsmentioning
confidence: 65%
“…Ada beberapa cara yang umum digunakan dalam memperoleh derivat peptida, yakni a) hidolisis dengan enzim menggunakan pepsin, tripsin, papain, dan beberapa protease lainnya, b) fermentasi dengan menggunakan mikroba, c) kombinasi enzim dan mikroba dan d) food processing dengan perlakuan panas dan tekanan (Tu et al, 2018). Amin et al, (2019) melaporkan bahwa salah satu sayuran yang termasuk dalam famili cucurbitaceae, labu, merupakan sumber utama komponen bioakif yang memiliki manfaat yang positif terhadap kesehatan.…”
Section: B Substansi Penting Dalam Pangan Fungsionalunclassified